The thermochemical degradation of cork - Pereira, H (Wood Science and Technology, 1992)
. The thermochemical degradation of cork from Quercus suber L. was studied in the temperature range 150 ~ ~ in relation to mass loss, chemical composition and the influ- ence on the cellular structure. The degradation of cork is strongly dependent on temperature and mass losses become significant at 200~ (15% of initial dry weight) and increase rapidly for higher temperatures (27% at 250 ~ 49% at 300 ~ 62% at 350 ~ until ashing at 450 ~ The polysaccharides are the most heat sensitive components: at 200 ~ hemicelluloses disappear and cellulose is degraded to a considerable extent. Suberin is more resistant and degradation starts at approx. 250~ 300~ samples only contain 7% suberin. The cellular structure of cork is also significantly influenced by temperature. Upon heating, cells expand and the cell walls stretch, attaining at 250~ a maximum cell volume increase corresponding to a factor of approximately 2. Above 300 ~ the structure of cell walls is considerably changed and show profound physical damage; in the later stages of pyrolysis, a cellular structure is no longer observed.
Keywords: Cellular structure; Cork; mass loss (voyant); thermochemical degradation